Dynamic price estimation model for residential buildings per square meter in Surabaya: Analyzing the impact of construction costs, material quality, and Land Area - Kusnan, Kusnan; Widayati, Naniek; Ma’soem , Dadang M (International Journal of Innovative Research and Scientific Studies, 2025)
This study develops a dynamic price estimation model for residential buildings per square meter in Surabaya, focusing on key variables such as construction costs, material quality, land area, and building size. Using multiple linear regression analysis and the backward elimination method, this research identifies the most significant factors that influence housing prices in urban and suburban areas. The results show that construction costs and material quality have a positive impact on housing prices, while land area exhibits an inverse relationship with the price per square meter, particularly in peripheral areas of the city. The final model achieved an R² value of 0.685, indicating strong explanatory power. The findings provide valuable insights for real estate developers, policymakers, and urban planners in optimizing housing development strategies, promoting affordable housing, and improving market transparency in rapidly urbanizing regions. This model can be applied in other emerging markets with similar urban dynamics.